Assuming we know that : $$\sum_{n=1}^{+\infty}{\frac{1}{n^2}} = \frac{\pi^2}{6}$$

How do you find the sum of a series where all terms are in this one ?

For instance, how do you prove that ?$$\sum_{n=1}^{+\infty}{\frac{1}{(2n-1)^2}} = \frac{\pi^2}{8}$$

  • $\begingroup$ The question has no answer, except that the sums one can realize are some (but not all) numbers in $[0,\pi^2/6]$. The specific instance in the second part of the question is answered below. $\endgroup$
    – Did
    Oct 14, 2012 at 9:17
  • $\begingroup$ The first sum is absolutely convergent, so you may reorder the terms. Consider splitting into even and odd terms and the second sum follows almost instantly. $\endgroup$
    – fretty
    Oct 14, 2012 at 9:30
  • $\begingroup$ By the way, $\pi^2/8$ in the RHS of the second identity should be replaced by $(\pi^2/8)-1$. $\endgroup$
    – Did
    Oct 14, 2012 at 9:57
  • $\begingroup$ I changed the LHS. $\endgroup$
    – Cydonia7
    Oct 14, 2012 at 11:54

1 Answer 1


Observe that:

$$\sum_{n=1}^{\infty} \frac{1}{n^2} = \sum_{n=1}^{\infty}\frac{1}{(2n)^2} + \sum_{n=1}^{\infty}\frac{1}{(2n-1)^2} = \frac{\pi^2}{6}$$


$$\sum_{n=1}^{\infty} \frac{1}{(2n)^2} = \frac{1}{4}\sum_{n=1}^{\infty}\frac{1}{n^2} = \frac{\pi^2}{24} $$

therefore \begin{eqnarray*} \sum_{n=1}^{\infty} \frac{1}{(2n-1)^2} & = & \sum_{n=1}^{\infty} \frac{1}{n^2} - \sum_{n=1}^{\infty} \frac{1}{(2n)^2} \\ & = & \frac{\pi^2}{6} - \frac{\pi^2}{24} \\ & = & \frac{\pi^2}{8} \end{eqnarray*}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.